2022
DOI: 10.1177/13634615221100377
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural adaptation of four instruments to measure stigma towards people with mental illness and substance use problems among primary care professionals in Chile

Abstract: Stigma toward people with mental illness and substance use problems is a significant global concern, and prevents people with these conditions from accessing treatment, particularly in primary health care (PHC) settings. Stigma is a cultural phenomenon that is influenced by particular contexts and can differ by country and region. The majority of stigma research focuses on Europe or North America leading to a lack of culturally relevant stigma research instruments for the Latin American context. The present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Self-reported behavioral health data are known to have dependability issues, even when compared to self-reported, non-behavioral health data (World Health Organization, 2022). In behavioral health, data quality is eroded by non-response, misreporting, errors in patient self-recall, and variance presented by the reliability and validity of instruments designed to measure addiction and substance use in cultures where the tool has not been validated (Ondersma et al, 2019;Parra Videla et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Self-reported behavioral health data are known to have dependability issues, even when compared to self-reported, non-behavioral health data (World Health Organization, 2022). In behavioral health, data quality is eroded by non-response, misreporting, errors in patient self-recall, and variance presented by the reliability and validity of instruments designed to measure addiction and substance use in cultures where the tool has not been validated (Ondersma et al, 2019;Parra Videla et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The study confirmed the presence of stigma toward people with MISUI. In addition, it (1) adapted and validated instruments to measure stigma among PHC providers in Chile ( 71 ), and (2) identified key elements to be considered for designing an effective intervention to reduce that stigma. In addition, it explored feasibility of the Canadian intervention.…”
Section: Introductionmentioning
confidence: 99%